2010
DOI: 10.1177/0192636510387826
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of an Urban District’s Adolescent Literacy Reform

Abstract: Weick's theory of sensemaking is used to analyze findings from a qualitative study of the implementation of a district-initiated adolescent intervention literacy course in two urban secondary schools. The authors concluded that implementation of the literacy course was hampered because district administrators, building leaders, teachers, and students all constructed multiple meanings of the course's purpose and priority within the district. Teachers expected to implement the initiative constructed their identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Two-way communication influenced by a high degree of trust (more on this below), creates a sense of ownership in accomplishing group goals (Cox and McLeod, 2014;Patterson et al, 2010). In addition to traditional methods of communication, social media provides opportunities for network members to share knowledge among themselves and with others on a regular basis (Cox and McLeod, 2014).…”
Section: Network Healthmentioning
confidence: 99%
“…Two-way communication influenced by a high degree of trust (more on this below), creates a sense of ownership in accomplishing group goals (Cox and McLeod, 2014;Patterson et al, 2010). In addition to traditional methods of communication, social media provides opportunities for network members to share knowledge among themselves and with others on a regular basis (Cox and McLeod, 2014).…”
Section: Network Healthmentioning
confidence: 99%
“…Twenty studies included data about students' experiences of curriculum and instruction in RICs (Bippert, 2019;Cantrell & Rintamaa, 2020;Cantrell et al, 2017;Frankel, 2016;Gerber et al, 2014;Ginsberg, 2020;Goering & Baker, 2010;Gomez et al, 2004;Greenleaf et al, 2001;Harmon et al, 2016;Houchen, 2013;Learned, 2016;Masterson, 2020;O'Brien et al, 2007;Paterson & Elliott, 2006;Patterson et al, 2010;Sarroub & Pernicek, 2014;Skerrett, 2012;Wexler et al, 2015;Wissman et al, 2012). The majority of studies reported on students' highly variable experiences in RICs, with many students responding in different ways, even when using the same program or approach, within the same school, or within the same classroom.…”
Section: Curriculum and Instructional Practicesmentioning
confidence: 99%
“…Relevance. Eighteen studies addressed students' perspectives about the relevance of curriculum and instruction in RICs to their current or future lives (Bippert, 2019;Cantrell & Rintamaa, 2020;Cantrell et al, 2017;Frankel, 2016;Gerber et al, 2014;Ginsberg, 2020;Goering & Baker, 2010;Gomez et al, 2004;Greenleaf et al, 2001;Harmon et al, 2016;Learned, 2016;Masterson, 2020;O'Brien et al, 2007;Paterson & Elliott, 2006;Patterson et al, 2010;Skerrett, 2012;Wexler et al, 2015;Wissman et al, 2012). Classes that students thought were relevant tended to be taught by teachers who had some level of flexibility, and where skills and strategies were contextualized within broader purposes and practices that students perceived to be meaningful.…”
Section: Curriculum and Instructional Practicesmentioning
confidence: 99%
“…The findings suggest the importance of allocating time for teachers to participate in sensemaking around issues of likely incoherence. Patterson, Eubank, Rathbun, and Noble (2010) also applied the sensemaking framework to understand how the perceptions of teachers, principals, central office administrators, and students related to a literacy intervention and influenced implementation. They found that each stakeholder made sense of the course in different ways regarding the rationale for adopting the program, how to implement the course, and its effectiveness in supporting students' literacy skills, therefore influencing how the course was implemented by teachers.…”
Section: Theoretical Frameworkmentioning
confidence: 99%